Asymbiotic seed germination and multiplication of an endangered orchid – Paphiopedilum venustum (Wall. ex Sims.) - Saranjeet Kaur; Kamlesh Kumar Bhutani (Acta Societatis Botanicorum Poloniae, 2016)
The present study was intended to facilitate ex situ conservation of Paphiopedilum venustum, a highly floriferous endangered terrestrial orchid species. A protocol was established for in vitro propagation and shoot multiplication. The cultures were initiated through asymbiotic seed germination technique, using undehisced and dehisced capsules. Four defined asymbiotic orchid seed germination media (terrestrial orchid medium, modified terrestrial orchid medium, Malmgren modified terrestrial orchid medium, Knudson C medium) were evaluated for their effectiveness in achieving maximum seed germination and early seedling development. The effect of darkness and 12-h photoperiod was also tested. Optimum seed germination, i.e., 82.7% was achieved on modified terrestrial orchid medium under a 12-h photoperiod using seeds from undehisced capsules. Shoot multiplication was accomplished using organic [peptone (1.0, 2.0 g L−1)] and inorganic [banana homogenate (10, 20, 30 g L−1) and potato powder (5.0, 10 g L−1)] growth supplements. Peptone at 1.0 g L−1 was the most effective in multiplying the shoots. Plantlets were acclimatized in the greenhouse with 80% survival frequency.